Pemetaan Tabel Relationship dalam Visualisasi Diagram Relasi untuk Eksplorasi Data Pada Database - Siti Julaeha; Nunu Kustian; Dudi Parulian (Universitas Indraprasta PGRI Jakarta, 2020)
Visualization is a tool that makes it easy to understand the information presented in charts and graphs. The purpose is to facilitate data exploration. Therefore, the authors use relationship diagrams as Mathematical Modeling to explore data that has a relationship between tables. The purpose of the study is to map the dataset, which found out a possibility that some errors when entering data. In the mapping process, we use the composition of relations, thus making the number of possible relationships in the mapping. Because of the problem, the table mapping use into a binary relationship diagram based on the number of attributes in a table. The conclusion obtained when using a binary relation diagram is that the more column in a table, the more mapping relationship diagrams must be drawn. Although the relationship diagram becomes very complex, it handled if the tables are correctly normalized.